Vibrant pasts in museum drawers: Advances in the study of late precolonial (AD 800–1500) materials collected from north-central Venezuela. Issue 1 (2nd January 2019) - Antczak, Andrzej T.; Antczak, Ma Magdalena; Falci, Catarina Guzzo
ABSTRACT: Starting in the second half of the nineteenth century, museums and private collectors across the Americas and Europe began amassing objects produced by the indigenous peoples of north-central Venezuela before the European conquest. The rich imagery displayed on decorated pottery and figurines, as well as on skilfully made body ornaments, strongly appealed to the aesthetic tastes of the museum curators and visitors of that time. With some laudable exceptions, most of the excavations that expanded these collections did not follow the archaeological practice standards of our time and did not leave behind any written reports. In consequence, these objects and associated data have remained disconnected from subsequent advances in regional archaeology. In this paper, we provide a general overview of the diverse archaeological collections from the region under study and insert them, critically, into the current understanding of north-central Venezuelan archaeology. We go on to focus on body adornments in order to show how microwear analysis of their production, along with the use wear traces they exhibit, combined with data concerning raw material procurement and depositional contexts, can shed light on the intricacies of the social life of these objects. We argue that up-to-date knowledge of regional archaeology interwoven with new interdisciplinary approaches on museum collections enables researchers to resuscitate the vibrant indigenous pasts lying in museum drawers.